PERJUMPAAN ISLAM DAN KATOLIK (Upaya Mencari Akar Epistemologi Tentang Konsep Keselamatan) - Abdullah Muthalib (Jurnal Sosiologi Reflektif, 2015)
Every religion has a concept of salvation based on transcendent values of the religion. Islam as a religion of revelation has the concept of salvation based on the messages contained Allah in the Qur’an and Hadith of the Prophet are valid. With reference to the ethical principles of Islam, the doctrine of salvation is the main point ranging in religion, with this principle, people feel the need to claim to believe and submit to the values of the revealed God. A person of faith is essentially aims to achieve safety, both in his life on earth and in the Hereafter. In the Catholic Christian religion also found a number of principles are the same theology that is taught about the importance of safety. In the book of the old covenant and new covenant be emphasized that the safety ranging point in the theology. In Islam and Catholicism, the concept of divinity is the same both believe in Almighty God (monotheism). Both believe that Isa (Jesus) and Muhammad. As the bearer of divine revelation. Although Islam to explain the concept of the deity in various contexts and meanings, while the Catholic meaning of salvation is placed in a variety of different verses, but the meaning remains the same.